The use of technology to protect the health of athletes during sporting competitions in the heat - Muniz-Pardos, B.; Sutehall, S.; Angeloudis, K.; Shurlock, J.; Pitsiladis, Y. P. (Frontiers in Sports and Active Living, 2015)
During the 2019 IAAF World Championships in Athletics in Doha and the 2020 Olympic Games in Tokyo, minimum daily temperatures are expected to be in excess of 30.C. Due to the metabolic demands of the sporting events and the high environmental temperatures, the risk of exertional heat stroke (EHS) is high. Careful planning by event organizers are needed to ensure that athletes are protected from irreversible long-term health damage, or even death during sporting competitions in the heat. Efforts typically have included standard medical plans, equipment, protocols, and expert medical teams. In addition, the importance of responding quickly to a hyperthermic athlete cannot be understated, as minimizing treatment time will greatly improve the chances of full recovery. Treatment time can be minimized by notifying medical personnel about the health status of the athlete and the extent of any pre-competition heat acclimatization. Technology that allows the live transmission of physiological, biomechanical, and performance data to alert medical personnel of potential indicators of EHS should be considered. Real time monitoring ecosystems need to be developed that integrate information from numerous sensors such as core temperature-monitoring "pills" to relay information on how an athlete is coping with competing in intense heat. Medical/support staff would be alerted if an athlete's responses were indicating signs of heat stress or EHS signs and the athlete could be withdrawn under exceptional circumstances. This technology can also help provide more rapid, accurate and dignified temperature assessment at the road/track side in medical emergencies.